Pengaruh Latihan Passing Berpasangan terhadap Akurasi Passing Atas Peserta Ekstrakurikuler Bola Voli di SMA Negeri 1 Adonara - Xaverius Mangu Hurung, Hendrikus; Bao Wolo, Hironimus; Cendrawati, Astuti (Social Science Academic, 2023)
The purpose of this study was to determine the effect of pair passing training on passing accuracy of extracurricular participants at SMA Negeri 1 Adonara. The research method used is quantitative descriptive with the nature of this study is associative. Descriptive quantitative research uses a correlational research approach. The subjects of the study were extracurricular participants of SMAN 1 Adonara totaling 26 students. The data collection technique uses form assessment of exercise quality and accuracy of top passing and documentation. Data analysis techniques use quantitative descriptive, assumption tests and hypothesis tests. The results showed that pair passing had a significant effect on the accuracy of upper passing in volleyball extracurricular participants at SMAN 1 Adonara. Based on the results of statistical calculations and test criteria, it can be known that t calculate 0.725 > t table 0.685 with a statistical calculation significance level of 0.00 < alpha 0.05, so that H0 is rejected and Ha is accepted.